Depression and Deviant Behavior: An Empirical Study of Psychological Strain Among Youth in Pakistan - Aleesha Sajjad; Muhammad Ramiz Mohsin; Malik KaleemUllah (Social Science Review Archives, 2025)
This study considers the selected research questions presented in the paper by analyzing key social and behavioral factors in a specific institutional and contextual environment. This study is based on a quantitative research design and aims to empirically assess the relationship between the identified independent and dependent variables using structured survey data collected from eligible respondents. To ensure consistency and reliability, data were collected using a standardized questionnaire based on a Likert scale format. Statistical analysis was carried out using the Statistical Package for the Social Sciences (SPSS). Descriptive statistics were employed to summarize respondents’ characteristics and perceptions, while inferential statistical techniques were used to examine the relationships among the study variables. The results indicate significant relationships between the main variables, highlighting the practical and theoretical importance of the research problem studied. Statistical analysis using Pearson's correlation was performed to examine the relationship between depression and deviant behaviors. The results revealed a statistically significant positive relationship between depression and deviant behavior. The study contributes to the existing literature by providing context-specific empirical evidence and offers practical implications for policy, institutional management and future research. By addressing an understudied area in a local context, the study adds value to applied social science research and supports evidence-based decision-making.